IMPLEMENTASI PENGADAAN TANAH UNTUK KEPENTINGAN UMUM DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (Studi Kasus di Kecamatan IV Jurai Kabupaten Pesisir Selatan) - Srimarwidiati Srimarwidiati; Maryati Bachtiar; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Land acquisition for development in the public interest is an activity to acquire land, inthe context of fulfilling land needs for development in the public interest, as well as providingcompensation to land owners affected by the activity and releasing legal relations from landowners to other parties, namely the government. The purpose of land acquisition is to provideland for the implementation of development in order to improve the welfare and prosperity ofthe nation, state, and society while still guaranteeing the legal interests of the entitled parties.This research is a type of sociological or empirical research. Empirical legal research islegal research that serves to look at the law in a tangible sense and examine how the law worksin the community. This research was conducted in District IV Jurai. Then the population andsamples are parties related to land acquisition activities, with primary data sources, secondarydata, and tertiary data, as well as data collection techniques used, namely interviews andliterature studies.From the results of this study, it can be concluded that the first is that the implementationof land acquisition for development for the public interest in the perspective of law number 2 of2012 has not been fully implemented properly, then, the two factors inhibiting land acquisitionfor the public interest are people who do not agree with the compensation offered, and the lackof understanding of the community about the importance of development, and the government islacking in socializing to the community. The three efforts made by the government are byholding re-public consultations or by re-deliberation with people who refuse compensation. Keywords: Land Acquisition, Public Interest